Business plan and entrepreneurship: contribution to strengthening tourism in the Sucre-San Vicente destination - Lemoine-Quintero, Frank; Montesdeoca-Calderón, María; Hernández-Rodríguez, Norma (Gestionar: revista de empresa y gobierno, 2023)
Business plans need to become an effective tool to ensure the sustainability of businesses. This is because, in order to achieve business objectives and expand in the market, it is crucial for these plans to include an economic-financial analysis. In the process of developing business plans, marketing and technology play a fundamental role. The objective was to develop a diagnosis in the enterprises of the sector to verify the accuracy of business plans at the activity level located in the cantonal headlands of Leónidas Plaza, Bahía de Caráquez, and San Vicente. The research was both qualitative and quantitative, and it examined the relationship between the elements of the field and the research object. The descriptive analytical method helped to generate strategic criteria regarding business plans and entrepreneurship. The study population consisted of business owners located in the communities within the scope of Bahía Extension because of their representativeness in the destination and tourist influx. A sample of 26 individuals was selected through non-probabilistic simple random sampling. The applied survey was found to be reliable, with a Cronbach's Alpha of 0.934 and 0.925 for the independent and dependent variables, respectively. This data provides insights that can be used to make decisions to develop functional and sustainable strategies for a sustainable tourist destination.
Keywords: Business plans, sustainability, positioning, investment, tourist destination; business plans; sustainability; positioning; investment; tourist destination